Disclosive Data: Who uses it, why, and what difference does it make? - Engeli, Andrew; Tolland, Aidan (International Journal of Population Data Science, 2019)
The Secure Research Service of the Office for National Statistics provides secure access to sensitive detailed data that are not publicly available. It provides access for Approved Researchers working on defined and approved projects, which serve the public good, within the framework of the Digital Economy Act 2017. SRS data can’t be downloaded, but users can access the data at their desk if they are part of a government organisation (subject to connection criteria being met), or in an Office for National Statistics (ONS) approved Safe Setting if not. In this paper, we examine the 2,612 projects that have been run using disclosive data through our service since its inception in 2002, and we map out patterns of data usage. In particular, we are interested in understanding; Who are the primary users of disclosive data for research (internal ONS, academics, OGD, charities, commercial users)? What are the primary sectors of research interest for which disclosive data access is requested? (Business, labour market, education, trade, health, population, etc.)? What are the predominant patterns of team working? (single researcher, multi-researchers)? What are the methodologies used to analyse the data? What statistical tools are being used in carrying our projects? Where are the researchers conducting the analysis based (NUTS1,2,3 classification)? What are the outputs and impacts of disclosive data research? The paper will conclude by proposing a classification of research projects based on a Hierarchical Cluster Analysis of the dataset collated for this presentation.